Valorization of solketal synthesis from sustainable biodiesel derived glycerol using response surface methodology - Arun, G. (MDPI, 2021)
Biodiesel production has gained considerable importance over the last few decades due to the increase in fossil fuel prices as well as toxic emissions of oxygen and nitrogen. The production of biodiesel via catalytic transesterification produces crude glycerol as a co-product along with biodiesel, amounting to 10 of the total biodiesel produced. Glycerol has a low value in its impure form, and the purification of glycerol requires sophisticated technologies and is an expensive process. The conversion of crude glycerol into value-added chemicals such as solketal is the best way to improve the sustainability of biodiesel synthesis using the transesterification reaction. Therefore, the conversion of crude glycerol into the solketal was investigated in a batch reactor simulation model developed by the Aspen Plus V11.0. The non-random two liquid theory (NRTL) method was used as a thermodynamic property package to study the effect of four input ketalization parameters. The model was validated with the findings of previous experimental studies of solketal synthesis using sulfuric acid as a catalyst. The influence of the following operating parameters was investigated: reaction time of 10,000 to 60,000 s, reaction temperature of 303 to 323 K, acetone to glycerol molar ratio of 2:1 to 10:1, and catalyst concentration of 0.005 to 0.03 wt . The optimum solketal yield of 81.36 was obtained at the optimized conditions of 313 K, 9:1, 0.03 wt , and 40,000 s. The effect of each input parameter on the ketalization process and interaction between input and output parameters was investigated by using the response surface methodology (RSM) optimizer. The relationship between independent and response variables developed by RSM fit most of the simulation data, which showed the accuracy of the model. A second-order differential equation fit the simulation data well and showed an R2 value of 0.99. According to the findings of RSM, the influence of catalyst amount, acetone to glycerol molar ratio, and reaction time were more significant on solketal yield. The effect of temperature on the performance of the reaction was not found to be significant because of the exothermic nature of the process. The findings of this study showed that biodiesel-derived glycerol can be effectively utilized to produce solketal, which can be used for a wider range of applications such as a fuel additive. However, further work is required to enhance the solketal yield by developing new heterogeneous catalysts so that the industrial implementation of its production can be made possible. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.